Inovasi Entrepreneurship Lembaga Bantuan Hukum (LBH) untuk Pencegahan Tindak Pidana Anak di SMA Al Islah Kecamatan Sukadiri - Ijum Setiawan; Muflih Adi Laksono (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
This study examines the innovative role of the Legal Aid Institute (LBH) in preventing juvenile crime through an entrepreneurship-based approach in the school environment. The urgency of this research stems from the increasing number of legal cases involving children, which have long-term social and psychological consequences. The purpose of this study is to design and evaluate the LBH preventive model at Al Islah High School, Sukadiri District, Tangerang Regency, which integrates legal literacy, restorative justice, and social entrepreneurship activities. The study used a qualitative descriptive method with students as the main focus, supported by a SWOT analysis. The results show that LBH is able to expand its role from reactive legal assistance to proactive prevention through legal literacy programs and entrepreneurship activities that build discipline, responsibility, and social awareness. Furthermore, there are nine strategies that can be implemented for the implementation of the Legal Aid Institute's (LBH) Entrepreneurship Innovation for the Prevention of Juvenile Crime in the future. The 9 strategies include aspects of optimizing human resources and volunteers, strengthening partnership networks, branding and positive publications, building internal management systems, diversifying funding sources, regular evaluations, innovating digital advocacy services, improving public education programs, taking part in current issues, building strong legal standing, increasing solidarity and support networks, and implementing strict advocacy ethics.